Teori Pembelajaran Kognivistik dan Aplikasinya dalam Pendidikan Islam - Hafidzulloh S M; Khoirotul Ni'amah (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2021)
Learning theory will make easier for educators to carry out the form of learning that will be implemented. This article will review the theory of cognitive learning and will provide a complete understanding and explanation so that it can be applied in learning activities. This study uses a qualitative approach and includes library research. The author tries and strives to collect library data related to the cognitive theory of J. Bruner, Ausubel, and Robert M. Gagne and their actualization in Islamic Education learning enriched from several academic sources both from books, scientific articles, previous studies and other scientific writings that related to the topic of this article. The results of this study are the cognitive theory developed by J. Bruner states cognitive processes are enactive, iconic, and symbolic; Ausubel said cognitive processes occur. Advanced organizer (initial arrangement), progressive differentiation, Reconciliation reconciliation (integrative reconciliation), consolidation; Robert M. Gagne states that cognitive processes are through receptors, sensory registers, short-term memory, long-term memory, and response generators. The learning process according to cognitivism is through the stages of assimilation, accommodation, and equilibration, namely the learning process is more directed. This is adjusted to the age of the students, so the stages are enactive, econic, and symbolic.